LncRNA DNAJC3-AS1 Regulates Fatty Acid Synthase via the EGFR Pathway to Promote the Progression of Colorectal Cancer - Tang, Yanyan; Tang, Rui; Tang, Mengtian; Huang, Ping; Liao, Zhiqiang; Zhou, Jumei; Zhou, Lianqing; Su, Min; Chen, Pan; Jiang, Jiarui; Hu, Yingbin; Zhou, Yujuan; et al. (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common cancer in the world. Recent studies have shown that Long non-coding RNA (lncRNA) involved in tumorigenesis and development in colorectal cancer. By constructing lncRNA differential expression profile, we screened from the gene chip that DNAJC3-AS1 is highly expressed in CRC tissues and is associated with poor prognosis in patients with CRC. We further proved through assays such as wound healing, colony formation, and CCK-8 that after interfering with DNAJC3-AS1 can reduce the proliferation, migration, and invasion of CRC cells. Mechanically, we found that DNAJC3-AS1 regulates fatty acid synthase to promote the progress of CRC via the EGFR/PI3K/AKT/NF-κB signaling pathway. Therefore, DNAJC3-AS1 may be a new target for the diagnosis and therapy of CRC.